Doença como experiência: as relações entre vulnerabilidade social e corpo doente enquanto fenômeno biocultural no estado do Pará - SILVA, Ariana Kelly Leandra Silva da (Universidade Federal do Pará, 2013)
This study examines the biosocial representation of individuals with Sickle Cell Anemia (SCA) in Pará State, Brazil, considering that this as a biocultural phenomenon, involving evolutionary, genetic, environmental, socioeconomic and cultural aspects of their daily life. The research deals with the sociability and the health issues of forty people with SCA, representing 10% of the States' cases, contacted in the Fundação Hemopa, Belém, the reference center for blood disorders in the State. The research encompasses their routine situation of social vulnerability, their perceptions of Health and Disease, treatments (Western and Folk Medicine), diagnostic, stigmas, prejudices, taboos and difficulties of access and accessibility to the services of SUS (the Brazilian National Health System). A comprehensive qualitative methodology and content analysis were used to understand the experience of persons who live daily with the instability and complexity of the disease. The personal experience of disease was uncovered though the formal conversations/interviews about the origins of the biological heritage, social relations, family entanglements and extra-familial dimensions of the individuals' in question, focusing on the evolution of SCA, especially considering the physical and psychological pain and other health complications experienced by the study's participants. The habitus in relation to their life ways is a category which includes the perception of the ethnic/racial nature of SCA, still perceived as "a disease that comes from the black people" with all its associated taboos. I conclude suggesting that many impacts of SCA are linked to the Social Determinants of Health and that there are important differences in relation to the susceptibilities of the persons, with many biosocial layers that require greater awareness by the political, clinical and primary care institutions responsible for the care of the affected citizens.